2014
DOI: 10.1002/adma.201402008
|View full text |Cite
|
Sign up to set email alerts
|

Interface Engineering for High‐Performance Top‐Gated MoS2 Field‐Effect Transistors

Abstract: Experimental evidence of the optimized interface engineering effects in MoS2 transistors is demonstrated. The MoS2/Y2O3/HfO2 stack offers excellent interface control. Results show that HfO2 layer can be scaled down to 9 nm, yet achieving a near-ideal sub-threshold slope (65 mv/dec) and the highest saturation current (526 μA/μm) of any MoS2 transistor reported to date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
271
2
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 295 publications
(301 citation statements)
references
References 49 publications
14
271
2
1
Order By: Relevance
“…The maximum mobility value of these 2D materials corresponds to a finite flake thickness when used in FET geometry, because the impact of the substrate can be eliminated through charge screening (117). Interface engineering has been employed through the use of hBN or Y 2 O 3 buffer layers to reduce surface roughness scattering and thereby enhance the mobility (118,119). Dielectric engineering using high-k material to increase the mobility, however, remains a controversial topic (120).…”
Section: Transition Metal Dichalcogenide Electronicsmentioning
confidence: 99%
“…The maximum mobility value of these 2D materials corresponds to a finite flake thickness when used in FET geometry, because the impact of the substrate can be eliminated through charge screening (117). Interface engineering has been employed through the use of hBN or Y 2 O 3 buffer layers to reduce surface roughness scattering and thereby enhance the mobility (118,119). Dielectric engineering using high-k material to increase the mobility, however, remains a controversial topic (120).…”
Section: Transition Metal Dichalcogenide Electronicsmentioning
confidence: 99%
“…1,2 For instance, graphene boasting good optoelectronic characteristics and high mechanical strength has large potential in energy conversion and storage [3][4][5] and transition-metal dichalcogenides (TMDs) with unique semiconducting properties are attractive to scalable digital field-effect transistors. [6][7][8] Furthermore, the chemical reactivity of 2D materials such as graphene oxide (GO) and TMDs has raised concerns and novel templates have been proposed to fabricate functional composites. [9][10][11][12][13][14][15][16][17] Black phosphorus (BP) has emerged to be an exciting member of the 2D family.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Molybdenum disulfide (MoS 2 ), one of the most studied TMDs, is an attractive 2D material with a thickness dependent band gap that has shown high device performance in a traditional top-gate field effect transistor (FET) structure. [5][6][7] Previous studies have shown high on/off ratios ($10 8 ), high mobility values (>200 cm 2 / Vs), and low subthreshold swing ($74 mV/dec) for top-gate MoS 2 devices, typically on SiO 2 . 8 The utilization of SiO 2 is often due to exfoliated MoS 2 having a high optical contrast on SiO 2 dielectric, allowing for quicker and easier detection of flakes.…”
mentioning
confidence: 99%